Les enfants d’Hildéric - Amélie Belleli (Cahiers Mondes Anciens)
Feminine fertility being of dynastical relevance, sources are specifically interested in births. The uterus perpetuates Roman blood, and he who is born from a mother shrouded in purple, can claim the throne. The existence of Roman-Barbarian alliances highlights the power women could wield in integrating the Empire. This “hyphen” role doesn’t elude Vandal king Genseric, as he arranges a marriage to Theodosian princess Eudocia for his son Huneric in 455. Clear proof of his aspirations, this union grants him a privileged bond with the Empire and the imperial power. Gemini diademetis heres, their son Hilderic embodies the continuity of the Theodosian blood. The feminine figure must be seen as a central element in these Roman-Barbarian marriages as she provides the Roman blood, which is passed on to potential children, despite the barbarian paternity. When Hilderic’s children arrive in Constantinople, Justinian and Theodora’s welcoming ratifies their illustrious roman kinship, over their Vandal lineage.